An unlikely revolutionary : Matsuo Takabuki and the making of modern Hawai'i : a memoir - Takabuki, Matsuo, 1923- (Honolulu : University of Hawai'i Press, 1998)
"Anyone interested in understanding the last fifty years of Hawai'i's economic and political history would do well to examine the life of Matsuo "Matsy" Takabuki. Actively involved in the Democratic Party during the post-World War II years, Takabuki was among a generation of Americans of Japanese Ancestry to rise to political office in the 1950s. A confidant of Governor John Burns, a member of the Board of Supervisors of the City and County of Honolulu, a business associate of developer and financier Chinn Ho, a trustee of the Bishop Estate - Takabuki has been at the heart of many of the sweeping social, financial, and political changes that have fundamentally altered Hawai'i in the last half century. An Unlikely Revolutionary is Takabuki's own story, told in his characteristically straightforward manner, of his life and work as one of the "movers and shakers" behind Hawai'i's transformation from an isolated, agriculture-based territory to a highly diverse, competitive modern community."--Jacket
Acknowledgments -- Introduction -- Prologue: Keiki o ka aina -- Chapter one. From Hawai'i's plantation to Europe's background -- Chapter two. Hawai'i after the war: A time for change -- Chapter three. At the heart of a revolution -- Chapter four. The financial revolution -- Chapter five. The Nisei trustee of the bishop estate -- Chapter six. Toward the Pacific Rim century -- Chapter seven. Reflections from inside Hawai'i -- Epilogue. As good as the next guy -- Appendix A. The 442nd Veterans Club: A president looks back on its first five years -- Appendix B. An address to the Hawaiian civic clubs -- Appendix C. Legacy of the princess: An address to the Oahu District Council of Hawaiian Civic Clubs -- Appendix D. Bishop estate today-The rest of you tomorrow -- Appendix E. Speech to National AJA veterans reunion -- Appendix F. 1991 Kamehameha Schools/Bishop estate service awards -- Chronology -- Index.
Includes index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Takabuki, Matsuo, -- 1923-; Takabuki, Matsuo, -- 1923-; Politicians -- Hawaii -- Biography; Hawaii -- Politics and government; Politiciens -- Hawaii -- Biographies; Hawaii -- Politique et gouvernement; BIOGRAPHY & AUTOBIOGRAPHY -- Political; Politics and government; Politicians; Hawaii; Politieke activiteit; Bedrijfsleven; Hawaii -- Politics and government -- 1959-; Politicians -- Biography -- Hawaii; Takabuki, Matsuo; Biography; Autobiography; autobiographies (literary works); Autobiographies; Biographies; Herinneringen (vorm); Biographies; Autobiographies; Biographies; Autobiographies